High Power Latent Heat Storages With 3D Wire Structures – Numerical Evaluation Of Phase Change Behavior. (October 2017) - Schlott, André; Hörstmann, Judith; Tittes, Knut; Andersen, Olaf; Meinert, Jens
Abstract: Latent heat storage devices use the melting enthalpy of a so-called phase change material (PCM) to store thermal energy. Open porous metals, such as 3D wire structures, allow the design of systems with tailored storage capacity and power. A geometric unit cell was identified, modelled and COMSOL Multiphysics was used to investigate the transient behavior of the PCM melting front within the composite of PCM and 3D wire structure. As a result, the impact of the wire structures material as well as the influence of brazing the inner connections of the wire structure on storage kinetics were analyzed.